The Body Doesn't Lie: Measuring Stress in Adventure Recreation Activities. (1st September 2016) - Ewert, Alan; Davidson, Curt; Chang, Yun
Abstract: This paper examines changes in levels of stress for individuals participating in a rappelling activity. Due to the inherent risk and physical nature of recreational activities such as mountaineering, rock climbing, and rappelling, it is often challenging to conduct research while participants are actually engaged in the activity. In this study, stress was measured by changes in cortisol within three different time frames (the day before the activity, during the activity, and upon conclusion of the activity). Using non-parametric procedures, results indicated significant differences in Cortisol levels between the various time frames and between male and female participants of the adventure-based program. These findings present new insights regarding what actually is occurring from a body chemistry perspective during an adventure recreation activity.